Migrating for children's better future: Intergenerational mobility of internal migrants' children in Indonesia - Alfariany Milati Fatimah; Chiara Kofol (University of Bonn, Center for Development Research (ZEF), 2019)
Internal migration dominates population mobility in Indonesia; according to the 2010 census, there were almost 30 million permanent migrants, around 12.5 percent of the population. The effects of this internal migration on the second generation continue to be under-explored. This paper investigates the long-term impact of parents' migration on their children's intergenerational per capita expenditure when adults. We argue that parental migration affects the human capital investment on their children, which has a direct impact on the children's outcomes when adults and on their deviation from the parents' economic status, hence their intergenerational mobility. We pooled the data of five waves of the Indonesian Family Life Survey, and we tackled the self-selection of parents' migration using linear regression with endogenous treatment. Our findings show that despite the fact that parental migration increases the education level of children and their per capita expenditure, it increases intergenerational mobility only when grown-up children live in urban areas, come from the poorest parents, and migrated themselves in their childhood. The left-behind children have more intergenerational mobility only if their father migrated, while there is no significant impact on intergenerational mobility if their mother migrated. The results are consistent with the persistence of individual inequality in Indonesia.
Keywords: J13; O15; 330; Migration; intergenerational mobility; children